1996
DOI: 10.1056/nejm199604043341402
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Factor Associated with Increased Glomerular Permeability to Albumin in Recurrent Focal Segmental Glomerulosclerosis

Abstract: A circulating factor found in some patients with focal segmental glomerulosclerosis is associated with recurrent disease after renal transplantation and may be responsible for initiating the renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
508
2
13

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(537 citation statements)
references
References 31 publications
14
508
2
13
Order By: Relevance
“…The pathologic variants and percentage of sclerotic glomeruli were also comparable between the two groups. These findings indicated that IgM deposition is not likely the initiation of FSGS lesion, which has been identified as several genes mutations or variants (9-13), circulating permeability factors (14)(15)(16), and others (17)(18)(19)(20)(21)(22)(23). However, IgM and complement-mediated injury may be secondary phenomena that occur after the primary renal insult.…”
Section: Discussionmentioning
confidence: 97%
“…The pathologic variants and percentage of sclerotic glomeruli were also comparable between the two groups. These findings indicated that IgM deposition is not likely the initiation of FSGS lesion, which has been identified as several genes mutations or variants (9-13), circulating permeability factors (14)(15)(16), and others (17)(18)(19)(20)(21)(22)(23). However, IgM and complement-mediated injury may be secondary phenomena that occur after the primary renal insult.…”
Section: Discussionmentioning
confidence: 97%
“…The pathogenesis of FSGS remains unclear but has been attributed to a 'circulating factor' present in the serum of patients with FSGS (2). Recurrence of FSGS after transplantation is not unusual and is most likely to occur in those recipients who have progressed rapidly to end-stage renal disease (ESRD) from the time of diagnosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the risk of recurrence when there has been a previous allograft failure due to recurrent FSGS may be as high as 80% (274,282,286,291). It has been shown by some investigators that the presence of an abnormal serum protein correlates with FSGS recurrence (286,292,293). However, standardized assays are not available for clinical use.…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%